COMMUNICATING URBAN HERITAGE THROUGH SOCIAL MEDIA IN TEGAL CITY - Hanifah Septianingrum; Didit Widiatmoko Soewardikoen; Agustinus Nur Arief Hapsoro (ADISAM Publisher, 2026)
Urban heritage plays an important role in shaping city identity and collective memory. In the digital era, social media has become a key platform for communicating cultural values and representing urban heritage to the public. This study examines how urban heritage is communicated through official social media accounts of Tegal City and explores audience preferences toward heritage-related digital content. Using a mixed qualitative approach, this research combines content analysis of social media posts with a survey of 104 respondents to identify dominant communication patterns, content types, and audience expectations. The findings indicate that social media communication in Tegal City is predominantly informational and promotional, with limited use of historical narratives and heritage-based storytelling. Meanwhile, audience preferences show a strong interest in clear narratives, consistent visual identity, and content that highlights historical and cultural values. The gap between current communication practices and audience expectations suggests that urban heritage has not yet been optimally positioned as a core element of the city’s digital representation. This study contributes to cultural and social science discussions by highlighting the role of social media in shaping public perceptions of urban heritage and city identity, particularly in medium-sized cities. The results underscore the importance of aligning digital communication practices with audience preferences to strengthen heritage-based urban representation.